Perbedaan Pengetahuan Ibu Balita Sebelum Dan Sesudah Dilakukan Penyuluhan Tentang Status Gizi Balita Umur 1-5 Tahun di Posyandu 1 Cokromenggalan Kecamatan Ponorogo Kabupaten Ponorogo - Hariyanto Hariyanto; Delya Putri Cahyani (Akbid Harapan Mulya Ponorogo, 2018)
Nutrition status is a condition of the body caused by the balance between nutrient intake and the needs. The balance can be seen from growth variable, such us body weight, height or body length, head circumference, and arm circumference. The purpose of this research was to know the difference of mothers' knowledge before and after counseling about nutritional status of children 1-5 years old in Posyandu 1 Cokromenggalan, Ponorogo Regency. This type of research was pre-experimental design. The method used Analytical Survey with Cross Sectional approach. The variables in this research were knowledge of mother toddler before and after counseling about nutrition status of children 1-5 years old. Data collected by questionaire. The population of 47 respondents and samples of 42 mothers who have under five years children using Accidental sampling technique in January 2017. The result of the research showed that the knowledge of the mother before counseling was 25 respondents (59,5%) in the sufficient category, the knowledge of mother after counseling was 30 respondents (71,4%) in good category. Based on the result of paired T test, the significance level 0.000 <0,05 so H0 was rejected, it mean there was difference knowledge of mothers' before and after counseling about nutritional status of children 1-5 years old. It is advisable to health workers to increase extension activities to under-five years children mothers to increase their knowledge and insight about nutritional status of toddlers age 1-5 years.